Targeted' Experiences of Racism in NSW after September 11, 2001 - Dreher, Tanja (UTS Shopfront Series, 2006)
Targeted researches experiences of racism in New South Wales after September 11, 2001. The monograph analyses data collected by the anti-racism hotline established by the Community Relations Commission For a Multicultural NSW (CRC). It details a significant increase in racially motivated violence and verbal abuse in NSW in the months following the US 2001 September 11 attacks and finds these incidents produced a climate of fear and insecurity, which continues to impact these communities, and denies them the chance to enjoy a true sense of Australian citizenship.